Cheirostylis acuminata (Orchidaceae; Cranichideae; Goodyerinae): a new species from Yunnan Province, China - Liu, Zhi-Long; Liu, Qiang; Gao, Jiang-Yun (Phytotaxa, 2016)
Cheirostylis Blume (1825: 413) is characterized by a column with two stelids, two well-separated stigma lobes and connate sepals that form a tube. There are about 55 species, mainly distributed in tropical Africa, through Southeast Asia, Japan, Indonesia and Pacific islands to Australia (Pridgeon et al. 2003, Chen et al. 2009, Bhattacharjee 2012, Govaerts et al. 2012). There are 18 species reported from China, of which 8 species are believed to be endemic (Averyanov et al. 2009, Chen et al. 2009, Lin & Lin 2009, Yang et al. 2013).